(untitled) (Discourse of Law and Administration, 2024)
The article is concerned with the current state and prospects of e-government development in Ukraine. The issue of development and improvement of e-government is of particular relevance during the war that was unleashed by Russia against Ukraine. Ukraine faced challenges caused by the destruction of government facilities and public services provision, energy supply, healthcare, communications, etc. Russian aggression is not slow to affect also the further development and improvement of the sphere of e-government. It became a reason for searching various ways to restore and protect the devastated infrastructure. At the same time, even in difficult circumstances, existing services have been improved and new applications have been created in the sphere of e-government in Ukraine. At the same time, there is a search for new opportunities related to the integration aspirations of Ukraine and the need to implement European norms and standards in the realization of the state information policy. Due to this fact electronic governance, along with other advantages, becomes a convenient mechanism that allows to achieve the specified goal in the shortest time. It is determined that the development of e-governance in Ukraine has been exposed significant changes, as evidenced by the extensive legislative system that exists today in the mentioned sphere. At the same time, it would be expedient to align and harmonize the existing legal system for e-government with relevant by-laws, enactments and instructions, for the most optimal and effective further functioning of it. At the present stage, electronic governance is able to create conditions for normal business development, improvement of the climate investment, economic growth, and also ensure the real participation of citizens in political processes, since the circumstances, the country found itself as a result of the war, require a quick and effective response to the challenges of the time. That is why Ukraine has already used the latest advanced technologies in this sphere and, in particular, applications that allow quickly respond to the challenges of time and provide full information to citizens about the environment, improve the quality of medical care in military medical institutions, allow evacuated citizens to access lost documents.